THE ROLE OF LEADERSHIP AND COMMUNICATION IN DISASTER EVACUATION MANAGEMENT: A CASE STUDY OF THE 2014 YELLOW FLOOD IN KELANTAN - Yaacob, Safar; Zainol, Noor Azmi Mohd; Hassan @ Ali, Suzana Ali; Ibrahim, Nora (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study concentrates on the role of leadership and communication in the success of evacuation operations during the 2014 Yellow Flood in Kelantan. Poorly defined leadership and communication structures were reported to have affected coordination and supply delivery during the operation. This study used a quantitative approach by distributing questionnaires to 750 respondents from major disaster response agencies in Malaysia. IBM SPSS 29.0 and SmartPLS 4.0 software were utilized in the data analysis. Results revealed that leadership factors (β = 0.430, p < 0.01) and communication (β = 0.520, p < 0.01) positively and significantly affect disaster evacuation. This indicates that both these factors are crucial to the effectiveness of disaster evacuation. This study contributes to the knowledge of the facets of human management in disasters and has policy and training implications for disaster management in Malaysia.